The process of the implementation of a dual language program in an elementary school in southwest Kansas - Espinoza, Pedro (Kansas State University, 2010)
The primary aim of this thesis is to examine the appropriate procedures needed to implement a Two Way Bilingual Immersion (TWBI) Program designed for an elementary school from grades K-4 and to make recommendations related to that process. Section I begins with an introduction to bilingual education and the different types of BE programs in the United States. It also examines the growth of these programs throughout the United States in recent years. Section II presents a general introduction to the characteristics and advantages of a TWBI program over other types of BE. The advantages and strategies presented here are intended to help teachers better understand the importance of using daily repetition of routine phrases, songs, and poems in their instruction, and the benefits to students in their overall academic progress as well. It also discusses the importance of language variation. Section III explores the implementation of a TWBI program in public schools. It highlights the importance of the selection of students, parental and community involvement, staff development and curriculum development. All of these factors are essential to having an effective program. Section IV presents a description of a specific TWBI program implemented in an elementary school in southwest Kansas. This section highlights many of the same components mentioned in Sections I-III as they apply to those being implemented in this specific school. This process can serve as a model for other schools interested in the implementation of a TWBI Program. Section V presents an explanation of second language acquisition and some of the advantages of learning a second language in a communicative classroom. Section VI presents my evaluation of five math and five reading activities used in a kindergarten class based on second-language acquisition theory. I also make some recommendations for pre and post activities, which can be used to activate the students’ schemata and check for comprehension.
Keywords: Dual language; Implementation procedures; Elementary school program; Two Way Bilingual Immersion (TWBI); Bilingual education; Language, Modern (0291)